-4(-18+6n)=-6(13n+15)

Simple and best practice solution for -4(-18+6n)=-6(13n+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-18+6n)=-6(13n+15) equation:


Simplifying
-4(-18 + 6n) = -6(13n + 15)
(-18 * -4 + 6n * -4) = -6(13n + 15)
(72 + -24n) = -6(13n + 15)

Reorder the terms:
72 + -24n = -6(15 + 13n)
72 + -24n = (15 * -6 + 13n * -6)
72 + -24n = (-90 + -78n)

Solving
72 + -24n = -90 + -78n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '78n' to each side of the equation.
72 + -24n + 78n = -90 + -78n + 78n

Combine like terms: -24n + 78n = 54n
72 + 54n = -90 + -78n + 78n

Combine like terms: -78n + 78n = 0
72 + 54n = -90 + 0
72 + 54n = -90

Add '-72' to each side of the equation.
72 + -72 + 54n = -90 + -72

Combine like terms: 72 + -72 = 0
0 + 54n = -90 + -72
54n = -90 + -72

Combine like terms: -90 + -72 = -162
54n = -162

Divide each side by '54'.
n = -3

Simplifying
n = -3

See similar equations:

| 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 | | 9(x-3)+3=-15 | | (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 | | N-1-3=-1 | | 2m+4n=12 | | 7(7r+19)=7-14r | | 12x+3=-10 | | -8x+4x+6x=-6 | | -12x+2y=-14 | | 3(7h-15)=9+18h | | -7(7-3x)=-175 | | 16x+8=-3 | | q/8-5=9 |

Equations solver categories